Biodiversity changes in abandoned military training areas: relationships to different management approaches in multiple taxa - Reif, Jiří; Chajma, Petr; Dvořáková, Lenka; Koptík, Jiří; Marhoul, Pavel; Čížek, Oldřich; Kadlec, Tomáš (Frontiers in Environmental Science, 2023)
Abandoned military training areas are biodiversity strongholds, and this is particularly true for open-habitat and threatened species in Central Europe. Such species benefited from a specific disturbance regime created by military activities that maintained small-grained environmental heterogeneity. However, the disturbance regime no longer occurs after abandonment and the biodiversity is at risk due to forest and shrub encroachment. To combat these adverse changes, several management options are used. As these options are not always applied for conservation purposes and differ in their implementation, it is essential to assess their impacts on biodiversity. We performed repeated standardized surveys (2009-2010, 2020-2022) of vascular plants, grasshoppers, butterflies and birds in 42 abandoned military training areas in Czechia, Central Europe. We calculated changes of species richness and abundance between periods for each taxon and related these changes to six different management types (woody plant cutting, mowing for conservation/agriculture, grazing for conservation/agriculture, vehicle movement) performed in these areas between periods. Vascular plants and grasshoppers showed positive changes, whereas the reverse was true for butterflies, and birds experienced mixed changes. Beta-diversity increased between periods (plants, grasshoppers, butterflies,) this increase was driven by extirpation of common species. Management impacts greatly different between types and taxa. Woody plant cutting showed positive impacts (plants and grasshoppers), while the impacts of both types of grazing were mixed (positive on plants and birds, negative on butterflies, mixed on grasshoppers). Mowing for agriculture supported plants and birds but had negative effects on grasshoppers. Mowing for conservation and vehicle movement were linked solely to negative biodiversity changes (former in plants, latter in butterflies). Some components of biodiversity (plants, grasshoppers), indicate that abandoned military training areas still serve as their strongholds and the management most likely contributes to this favourable state. In contrast, the pattern found for butterflies is worrying since the management performed up to now apparently does not meet their requirements, likely because they are based on smaller-scale habitat mosaic than currently occurs in the areas. Our results may serve as a guide for future prioritization of environmental management, and we urge for development of more nuanced approaches to save the butterflies.